The sexually dimorphic adipose fin is an androgen target tissue in the brown trout (Salmo trutta fario) - Hisar, Olcay; Sönmez, Adem Yavuz; Aras Hisar, Şükriye; Budak, Harun; Gültepe, Nejdet (Fish PHYSIOLOGY AND BIOCHEMISTRY 2013 Volume 39 Number 2, 2013)
An investigation has been described on the relationship of body length, age and sex with adipose fin length and the number of androgen receptor (AR)-containing cells in the adipose fin as a secondary sexual characteristic for brown trout (Salmo trutta fario). Firstly, body and adipose fin lengths of 2- to 5-year-old brown trout were measured. Thereafter, these fish were killed by decapitation, then their sexes were determined, and adipose fins were excised. The cellular bases of AR binding activities in the adipose fins were analyzed with an antibody against human/rat AR peptide. Immunocytochemistry and western blotting techniques were performed with this antibody. Analysis of morphological measurements indicated that body length and age had a linear relationship with adipose fin length. The coefficients of determination for the body length and age were 0.92 and 0.85 in the male fish and 0.76 and 0.73 in the female fish against the adipose fin length, respectively. At 2 years of age, cells in the adipose fin did not exhibit AR immunoreactivity. However, AR-immunopositive cells were abundant in the adipose fin of 3- to 5-year-old fish. Moreover, the number of AR-immunopositive cells was significantly (P\0.05) high in males and increased with age. These observations indicate that the adipose fin in the brown trout is a probable target for androgen action and that tissue function or development may to some extent be androgen dependent. In addition, it is likely that such an effect will be mediated by specific androgen receptors.
Keywords: Adipose fin , Androgen receptor ,Secondary sexual characteristic , Brown trout